BET Bromodomain Inhibitors Suppress Inflammatory Activation of Gingival Fibroblasts and Epithelial Cells From Periodontitis Patients - Maksylewicz, Anna; Bysiek, Agnieszka; Lagosz, Katarzyna B.; Macina, Justyna M.; Kantorowicz, Malgorzata; Bereta, Grzegorz; Sochalska, Maja; Gawron, Katarzyna; Chomyszyn-Gajewska, Maria; Potempa, Jan; Grabiec, Aleksander M. (Frontiers in Immunology, 2019)
BET bromodomain proteins are important epigenetic regulators of gene expression that bind acetylated histone tails and regulate the formation of acetylation-dependent chromatin complexes. BET inhibitors suppress inflammatory responses in multiple cell types and animal models, and protect against bone loss in experimental periodontitis in mice. Here, we analyzed the role of BET proteins in inflammatory activation of gingival fibroblasts (GFs) and gingival epithelial cells (GECs). We show that the BET inhibitors I-BET151 and JQ1 significantly reduced expression and/or production of distinct, but overlapping, profiles of cytokine-inducible mediators inflammation and bone resorption in GFs from healthy donors (IL6, IL8, IL1B, CCL2, CCL5, COX2 and MMP3) and the GEC line TIGK (IL6, IL8, IL1B, CXCL10, MMP9) without affecting cell viability. Activation of mitogen activated protein kinase and nuclear factor-κB pathways was unaffected by I-BET151, as was the histone acetylation status, and new protein synthesis was not required for the anti-inflammatory effects of BET inhibition. I-BET151 and JQ1 also suppressed expression of inflammatory cytokines, chemokines and osteoclastogenic mediators in GFs and TIGKs infected with the key periodontal pathogen Porphyromonas gingivalis. Notably, P. gingivalis internalization and intracellular survival in GFs and TIGKs remained unaffected by BET inhibitors. Finally, inhibition of BET proteins significantly reduced P. gingivalis-induced inflammatory mediator expression in GECs and GFs from patients with periodontitis. Our results demonstrate that BET inhibitors may block the excessive inflammatory mediator production by resident cells of the gingival tissue and identify the BET family of epigenetic reader proteins as a potential therapeutic target in the treatment of periodontal disease.